EFEKTIFITAS PENGELOLAAN ZAKAT UNTUK PEMBIAYAAN PENDIDIKAN MELALUI BEA SISWA SATU KELUARGA SATU SARJANA DI BAZNAS KABUPATEN DHARMASRAYA - Elvi Syoviana; Yahya Yahya (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
In increasing the capacity of students, education is needed. Education plays an important role in developing religious values and morals to participants. When people are poor and have no money to continue their education. So the role of zakat is very necessary to help the needs of these lectures. In dharmasraya district, the existence of effective and efficient zakat management through the One House One Sarjan (SKSS) program to finance students who are continuing their education is very helpful so that they can complete their education until they graduate and get a bachelor's degree. The purpose of the study was to determine the effectiveness of zakat management for education financing through SKSS scholarships at the dharmasraya district baznas. The method used was qualitative with a descriptive approach. Meanwhile, the results of the research show that the management of zakat through the SKSS program in the dharmasraya district has been running effectively and efficiently for education financing. This is evidenced that many have graduated and become undergraduates